FECTIVENESS OF USING HOSPITAL MANAGEMENT INFORMATION SYSTEMS (SIMRS) IN EMERGENCY INSTALLATION PATIENT SERVICES EMERGENCY (IGD) WITH A TECHNOLOGY APPROACH ACCEPTANCE MODEL (TAM) AT ALIYAH II HOSPITAL KENDARI CITY IN 2026 - Della Widyastika; Fitri Kurniawati; Noviani Munsir (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study aims to analyze the effectiveness of the Hospital Management Information System (HMIS) in supporting patient services at the Emergency Department of RSU Aliyah II Kendari using the Technology Acceptance Model (TAM) approach. This study employed a descriptive qualitative research design. The informants were selected through purposive sampling and consisted of information technology (IT) officers and healthcare workers who directly used the HMIS in the Emergency Department. Data were collected through in-depth interviews, observations, and documentation, and were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the Hospital Management Information System at the Emergency Department of RSU Aliyah II Kendari has been relatively effective. Based on the Perceived Ease of Use dimension, users considered the system easy to learn and operate. From the Perceived Usefulness perspective, the system improved service efficiency, facilitated access to patient information, accelerated healthcare processes, and reduced documentation errors. Furthermore, the Attitude Toward Using dimension showed that most users had a positive attitude toward the system and supported its continued use in healthcare services. However, several challenges were identified, including network disruptions, limited electrical capacity, and the need for continuous user training. Therefore, improvements in technological infrastructure and human resource capacity are necessary to optimize the implementation of the Hospital Management Information System and enhance the quality of patient services in the Emergency Department